Farmers' Perceptions of Integrated Farming Systems for Sustainable Agrotourism in Das Batu Lanteh Sumbawa, Indonesia: Persepsi Petani terhadap Sistem Pertanian Terpadu untuk Agrowisata Berkelanjutan di Das Batulanteh Sumbawa, Indonesia - Ahmadi, Sudarly; Widhiantari, Ida Ayu; Cicilia, Siska; Amaro, Moegiratul; Ayu, Hanifah; Ahmadi, Ahmadi; Amrullah, Amrullah (Indonesian Journal of Tropical Biology, 2025)
Integrated farming systems (IFS) offer a sustainable approach to optimize agricultural resources and support agro-tourism development in dryland regions. This study aims to analyze farmers' perceptions of IFS and its potential implementation for sustainable agro-tourism in the Batu Lanteh watershed, Sumbawa. Using a descriptive-analytical mixed-methods approach, data were collected through surveys of 30 purposively selected farmers across three villages, complemented by in-depth interviews and field observations. Results indicate that farmers partially adopt IFS practices such as using crop residues as feed, cultivating legumes, and recycling manure but face constraints due to limited agricultural literacy, small land holdings, aging farmers, and inadequate market access. Although economic benefits like increased income and reduced production costs are positively perceived, consistent implementation of long-term ecological practices remains low. The study concludes that enhancing IFS adoption and agro-tourism integration requires targeted technical assistance, farmer education, and improved infrastructure. These efforts can optimize resource use, strengthen environmental conservation, and promote sustainable agro-tourism in dryland contexts.